Kanon - ideologia i mechanika. Problematyka kanonu w rozrywce interaktywnej. - Gnat, Tomasz (Er(r)go. Teoria - Literatura - Kultura, 2017)
[abstrakt po polsku poniżej] Tomasz Gnat Institute of English Cultures and Literatures University of Silesia in Katowice Poland Canon – Ideology and Mechanics The Question of Canon in Interactive Entertainment Abstract: The analysis conducted in the paper focuses on the role, the reason, and interpretations of canon in the medium of interactive entertainment. The notion of canon is analysed from two perspectives. In the first part, the author interprets canon as an ideological foundation and investigates the influence of such a structure on the problem of digital preservation. In the second part, the mechanical application of canon (understood as overarching narrative structure) is examined. The discussion focuses on the analysis of attempts at reconciling this fixed structure with the necessity to introduce interactivity, an innate characteristic of the medium in question. The author does not encourage or discourage any attempts to form a video game canon; he is rather interested in the actual results and reasons for forming such constructs. The aim of the analysis is not only to emphasise certain specific circumstances concerning the question of canon in this medium, but also to improve our understanding of the issue of canon in post-modern media. Keywords: interactive entertainment, narration, preservation and protection of cultural heritage, canon Tomasz Gnat Instytut Kultur i Literatur Anglojęzycznych Wydział Filologiczny Uniwersytet Śląski w Katowicach Kanon - ideologia i mechanika. Problematyka kanonu w rozrywce interaktywnej Abstrakt: Przedstawiona w niniejszej pracy dyskusja skupi się na roli, racji bytu i interpretacjach pojęcia kanonu w rozrywce interaktywnej. Kanon będzie tu postrzegany z dwóch perspektyw. W pierwszej części, autor interpretuje kanon jako fundament ideologiczny i bada wpływ takiej struktury na problematykę zachowania dóbr kultury cyfrowej. W części drugiej, autor przyjrzy się kanonowi z perspektywy mechanicznej, jako nadrzędnej strukturze narracyjnej. Dyskusja skupi się na analizie prób pogodzenia sztywnych ram wyznaczonych przez kanon z koniecznością wprowadzenia interakcji, charakterystycznej dla omawianego medium. Ważnym jest by zaznaczyć, że autor nie podejmuje się tutaj obrony konieczności istnienia kanonu gier, ale też nie nawołuje do zaprzestania prób jego formowania. Wnioski płynące z przedstawionych tu rozważań mają raczej na celu zwrócenie uwagi na specyfikę medium rozrywki interaktywnej i, być może, będą mogły przyczynić się do lepszego zrozumienia tematyki kanonu w szerszej perspektywie dóbr kultury współczesnej. Słowa kluczowe: rozrywka interaktywna, narracja, ochrona dóbr kultury, kanon